Malaria Transmission and Vector Resistance to Insecticides in a Changing Environment: Case of Simbock in Yaoundé-City, Cameroon - Mbakop, Lili R.; Awono-Ambene, Parfait H.; Ekoko, Wolfgang E.; Mandeng, Stanislas E.; Nwane, Philippe; Fesuh, Betrand N.; Toto, Jean-Claude; Alenou, Léo D.; Onguina, Hugues G.; Piameu, Michael; Fomena, Abraham; Etang, Josiane (Frontiers in Tropical Diseases, 2022)
Ecological upheavals resulting from uncontrolled urbanization can lead to significant changes in vector borne diseases’ profiles, thus requiring a thorough revision of their prevention and control strategies. The current study aimed at characterizing malaria vector populations in the Simbock neighborhood of Yaoundé-city (Cameroon), in relation to its urbanization scheme. Adult mosquitoes were captured by human landing catches (HLC) in- and outdoors prior to (2000–2006) and during infrastructural development (2014–2016). Anophelines were morphologically identified and analyzed for Plasmodium (P.) falciparum circumsporozoite protein detection using the ELISA technique. Species of the Anopheles (An.) gambiae complex were identified using SINE-PCR. Adult An. gambiae s.l. from larvae collected between 2014 and 2017 were tested for susceptibility to insecticides (0.1% bendiocarb, 4% DDT, 0.75% permethrin and 0.05% deltamethrin) with or without piperonyl butoxide (PBO) synergist, using WHO standard bioassays. The Hot Oligonucleotide Ligation Assay was used to detect the knockdown resistance (kdr) L995F/S mutations. Overall, nine malaria vector species were identified in 2000-2006, mostly An. moucheti (49%), An. nili (13.5%) and An. gambiae s.l. (12%); the six remaining species were represented at less than 3% each. However, only three species were found in 2014-2016, with increasing proportions of An. gambiae s.l. (67%) and An. funestus (32%) (P<0.0001). An. gambiae s.l. consisted An. coluzzii (> 85%) and An. gambiae (<15%) species during the two study periods. Plasmodium falciparum infection rates were 2.1% and 1.0% in 2000-2006 and 2014-2016 respectively (P=0.4), with decreasing entomological inoculation rates (EIR) from 0.34 infective bites per man per night (ib/m/n) to 0.02 ib/m/n (P<0.0001). Anopheles gambiae s.l. was resistant to DDT and permethrin [<40% mortality rates (MR)], and deltamethrin (65-89% MR), but fully susceptible to bendiocarb (100% MR). Pre-exposure of mosquitoes to PBO resulted in 90-100% MR to deltamethrin but not to permethrin. Furthermore, the two kdr L995F/S resistance alleles were recorded at 0.64 and 0.006 frequencies respectively. This study highlights a shift from rural to urban malaria transmission in Simbock, coupled with DDT and pyrethroid resistance in An. gambiae s.l. Combination vector control interventions, e.g., PBO nets and bendiocarb indoor residual spraying are needed in such areas.